2019
DOI: 10.1123/ijspp.2018-0921
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sprint Performance With Inhaled Long-Acting β2-Agonists Combined With Resistance Exercise

Abstract: Purpose: To investigate the impact of twice-daily inhalation of 100 µg of salmeterol (SAL) or 12 µg of formoterol (FOR) in addition to a strength- and power-training program over a 5-wk period on a 30-m sprint, strength, power, mood, stress, and skinfold thickness. Methods: In a randomized, single-blind study, 23 male and 15 female nonasthmatic, recreationally active individuals were recruited (mean [SD] age 26.3 [5.4] y, weight 76.2 [11.5] kg, height 176.9 [8.5] cm). Participants completed 3 standardized whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The same is the case for salbutamol, which via the inhaled route has been shown to induce lipolysis at therapeutic doses and to increase resting metabolic rate . Lastly, daily inhalation of formoterol (12 μg twice daily) or salmeterol (100 μg twice daily) at therapeutic doses was recently shown to enhance sprint performance more than placebo during a 5‐week period of strength and power training, indicating that the dosing regimens applied were sufficient to induce muscular adaptations. Collectively, the pharmacologic and physiologic data available indicate that inhalation of beta 2 ‐agonist can exert anabolic and lipolytic actions and may be misused for leanness, at least at higher doses.…”
Section: Inhalation Of Beta2‐agonists At High Doses Exerts Similar Efmentioning
confidence: 88%
“…The same is the case for salbutamol, which via the inhaled route has been shown to induce lipolysis at therapeutic doses and to increase resting metabolic rate . Lastly, daily inhalation of formoterol (12 μg twice daily) or salmeterol (100 μg twice daily) at therapeutic doses was recently shown to enhance sprint performance more than placebo during a 5‐week period of strength and power training, indicating that the dosing regimens applied were sufficient to induce muscular adaptations. Collectively, the pharmacologic and physiologic data available indicate that inhalation of beta 2 ‐agonist can exert anabolic and lipolytic actions and may be misused for leanness, at least at higher doses.…”
Section: Inhalation Of Beta2‐agonists At High Doses Exerts Similar Efmentioning
confidence: 88%
“…A continuously growing body of evidence exists that the aerobic performance does not appear to be acutely affected by the use of β 2 ‐agonists such as terbutaline 126–128 . Conversely, β 2 ‐agonists such as salbutamol and salmeterol can enhance anaerobic performance concerning disciplines such as, for example, sprint 129–131 but not necessarily when used at dosages permitted according to WADA's regulations 132 . These regulations include maximum permitted doses for formoterol, salbutamol, and salmeterol, 10 with corresponding urinary thresholds existing for formoterol and salbutamol, 133 while salmeterol is reported as AAF when exceeding 50% of the MRPL (i.e., 10 ng/ml).…”
Section: β2‐agonistsmentioning
confidence: 99%
“…Early work in athletes suggested that used acutely at therapeutic low doses (50 µg), salmeterol did not enhance running performance, cycling anaerobic power or muscle strength 15,16 . However, more recent work has demonstrated that daily inhaled treatment with salmeterol (100 µg twice daily) enhanced 30 m sprint performance during a period of 5 weeks in combination with a power and strength program 17 . To our best knowledge, no study has been performed in humans that had muscle hypertrophy as an outcome measure, but studies in rodents show that salmeterol possesses anabolic properties.…”
Section: Salmeterol As a Performance Enhancing Drugmentioning
confidence: 99%